Sinergitas Alumni dan Pondok Pesantren Sunan Drajat Lamongan dalam Pemberdayaan Ekonomi Masyarakat - Luqmanul Hakim (Program Studi Ekonomi Syariah dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
Synergy of Alumni and Pondok Pesantren Sunan Drajat Lamongan in community economic empowerment is an article that seeks to answer the question how is the synergy of alumni and Pondok Pesantren Sunan Drajat Lamongan in empowering the community's economy, by reviewing the synergy of alumni and society in general in economic empowerment programs is very important because Islamic boarding schools are currently required to show collaboration so that Islamic boarding schools are not only able to graduate students who understand religious knowledge, but are also required to have broad knowledge, managerial abilities and expertise that is entrepreneurial in nature as a medium for mutualist symbiosis between alumni and Islamic boarding schools. This research is a field research with a qualitative approach that is descriptive analytical. The data collection technique uses interviews, observation and documentation about programs that synergize with alumni in economic empowerment. Then the data is processed and analyzed with a descriptive-inductive pattern. The results of this study indicate that there is an implementation of synergy by pesantren and their alumni in economic empowerment. With this synergy, it provides a wide space for pesantren to be able to develop their potential and vice versa, the implication is to create mutually reinforcing synergies between alumni and pesantren. Forms of empowerment can be seen in the pattern of relationships between the Sunan Drajat Lamongan Islamic Boarding School and alumni through economic empowerment using the triple helix theory model.